Do parenting styles matter? Perceived dimensions of parenting styles, creative abilities and creative self-beliefs in adolescents. (December 2020) - Gralewski, Jacek; Jankowska, Dorota Maria
Abstract: On a sample of 552 high school students, the present study investigated the relationships between perceived parenting dimensions, and children's creative abilities assessed by the Test for Creative Thinking-Drawing Production (TCT-DP) as well as their creative self-beliefs (i.e. creative self-efficacy and creative personal identity). Results indicated that the dimension of parental child acceptance and autonomy support were weakly but positively related to children's creative self-efficacy and creative personal identity. However, no statistically significant relationship was found between parental autonomy support and children's creative abilities. In this sense, this study provides preliminary evidence for the effect of parental style dimensions on children's creative self-beliefs. Implications and limitations of this study were discussed. Recommendations are also given to researchers for conducting further studies on the topic.